2019
DOI: 10.24203/ajas.v7i5.5917
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Saltwater Intrusion on the Fish Assemblage in the Middle Part of Shatt Al-Arab River, Iraq

Abstract: In 2018, a serious changes in the salinity of the Shatt Al-Arab river, as salinity intrusion progressed further to upper reaches of the river due to sharply decline in river flow. Therefore, the fish assemblage structure in the middle of the river, from  Sindbad and Abu Al-Khasibs was assessed during the period from January to December 2018. Fish were sampled by gill nets, cast net and electro-fishing from both sites. Salinity fluctuated from 2.0‰ (January) in both sites to 16.2 and 25.0% during Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
(28 reference statements)
1
19
1
Order By: Relevance
“…Conversely, Cichlids species are invasive fish to Iraqi waters, and early records show that Coptodon zillii caught from the Euphrates River, middle of Iraq during 2007, later other species, O. aureus and O. niloticus documented in the south of Iraq. Currently, these three species are well established and dominate the fish populations in various Iraqi waters [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Cichlids species are invasive fish to Iraqi waters, and early records show that Coptodon zillii caught from the Euphrates River, middle of Iraq during 2007, later other species, O. aureus and O. niloticus documented in the south of Iraq. Currently, these three species are well established and dominate the fish populations in various Iraqi waters [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It is represented by three species in the Iraqi waters namely Nile tilapia Oreochromis niloticus, Blue tilapia O. aureus and Redbelly tilapia Coptodonzillii which have invaded these waters during the last decade. Now, the tilapia species were found in different waters of the country [3][4][5][6][7][8][9][10][11][12]. The total landing of tilapia species by the inland artisanal fisheries of Basrah Governorate was 864,700 kg during 2017-2019 and came in the third rank with 15.4% of the total fish landings during this period [13].…”
Section: Introductionmentioning
confidence: 99%
“…Abdullah et al (2018) found that tilapia species formed 21.9% of fish structure in the Al-Sweib river, a tributary of the Shatt Al-Arab river during 2013-2015. Moreover, the tilapia species formed 32.3% of fish assemblage in the Shatt Al-Arab river at Abu Al-Khasib district (Mohamed & Hameed, 2019). Knowledge on the food, feeding habits and trophic interrelationships of fishes is essential to understand the life history of fishes including growth, behaviour, reproduction, migration and other vital activities of fishes, and also help to understand the predicted changes on the ecosystem due to natural or anthropogenic interventions (Priyadharsini et al, 2012;Sajeevan & Kurup, 2013).…”
Section: Introductionmentioning
confidence: 99%